A Systematic Literature Review of 21st Century Skills and Competencies in Primary Education - Chalkiadaki, Areti (International Journal of Instruction, 2018)
The current literature review the discussion of 21st century skills in the context of primary education. A sample of texts satisfying the predetermined inclusion criteria was analyzed (n = 40), with the aims of synthesizing the proposed frameworks that are most cited by authors interested in 21st century skills and competencies in primary education (n = 6) and the dimensions of the skills and competencies mostly emphasized and researched in the particular context, according to the literature review research questions. The results showed a particular interest in skills and competences related to the conditions of the information and communications technology development, globalization and the need for innovation. However, a need for research focusing specifically in the context of primary education was recognized.